2014
DOI: 10.1038/nsmb.2844
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the stabilization of MALAT1 noncoding RNA by a bipartite triple helix

Abstract: Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a highly-abundant nuclear long noncoding RNA that promotes malignancy. A 3′-stem-loop structure is predicted to confer stability by engaging a downstream A-rich tract in a triple helix, similar to the expression and nuclear retention element (ENE) from the KSHV polyadenylated nuclear RNA. The 3.1-Å resolution crystal structure of the human MALAT1 ENE and A-rich tract reveals a bipartite triple helix containing stacks of five and four U•A-U trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
271
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(288 citation statements)
references
References 49 publications
11
271
0
Order By: Relevance
“…The crystal structure of the MALAT1 ENE + A confirmed that the U-rich ENE coalesces with a downstream A-rich tract to form a bipartite triple helix, allowing MALAT1 to accumulate in cells (Brown et al 2014). Preceded by two A-minor triples, the first triplex segment consists of five U•A-U triples followed by a C•G-C triple, and the second triplex contains four U•A-U triples.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…The crystal structure of the MALAT1 ENE + A confirmed that the U-rich ENE coalesces with a downstream A-rich tract to form a bipartite triple helix, allowing MALAT1 to accumulate in cells (Brown et al 2014). Preceded by two A-minor triples, the first triplex segment consists of five U•A-U triples followed by a C•G-C triple, and the second triplex contains four U•A-U triples.…”
Section: Introductionmentioning
confidence: 86%
“…Most RNA triple helices identified to date rely heavily on canonical U•A-U and C•G-C triples (Brown et al 2014). However, the discovery of noncanonical triples in bacterial riboswitches, the group II intron, and the spliceosome suggests that other nucleotide combinations are possible (Gilbert et al 2008;Toor et al 2008;Hang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations